2009
DOI: 10.1364/oe.17.006813
|View full text |Cite
|
Sign up to set email alerts
|

One dimensional resonant Fibonacci quasicrystals: noncanonical linear and canonical nonlinear effects

Abstract: A detailed experimental and theoretical study of the linear and nonlinear optical properties of different Fibonacci-spaced multiple-quantum-well structures is presented. Systematic numerical studies are performed for different average spacing and geometrical arrangement of the quantum wells. Measurements of the linear and nonlinear (carrier density dependent) reflectivity are shown to be in good agreement with the computational results. As the pump pulse energy increases, the excitation-induced dephasing broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Similar features should be also manifested in phonon transport through superlattices with compositional disorder. Semiconductor heterostructures are very promising for the controllable study of the effect, because quantum cascade lasers with more than a thousand layers4647, as well as deterministic aperiodic photonic structures with hundreds of layers, are efficiently grown nowadays4849. Observation of very similar Fano resonances in opals22 calls for future theoretical analysis and hints that some of the effects studied here may unexpectedly survive even in 3D, even though localization phenomena in 1D and 3D systems are generally quite different 30…”
Section: Discussionmentioning
confidence: 85%
“…Similar features should be also manifested in phonon transport through superlattices with compositional disorder. Semiconductor heterostructures are very promising for the controllable study of the effect, because quantum cascade lasers with more than a thousand layers4647, as well as deterministic aperiodic photonic structures with hundreds of layers, are efficiently grown nowadays4849. Observation of very similar Fano resonances in opals22 calls for future theoretical analysis and hints that some of the effects studied here may unexpectedly survive even in 3D, even though localization phenomena in 1D and 3D systems are generally quite different 30…”
Section: Discussionmentioning
confidence: 85%
“…In particular, it was found that QPSs create localization of electronic states and their collective response differs from that of their constituents. While the linear wave phenomena in quasi-periodic media were extensively explored during the last few decades , nonlinear QPSs have been studied only recently [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Open Accessmentioning
confidence: 99%
“…The rst makes use of a projection from a higher-dimensional space, while the second employs the so-called substitutional sequences [11]. Being strictly quasi-periodic, the Fibonacci sequence can be obtained by using both of the above methods.…”
Section: Linear Transmission Of Fibonacci Photonic Crystalsmentioning
confidence: 99%